Transient Wheal Attack Corresponding to the Tumor Lesions of Primary Cutaneous Diffuse Large B Cell Lymphoma, Leg Type after Successive Rituximab Treatment - Saori Itoi; Atsushi Tanemura; Misa Hayashi; Naoko Nagata; Mamori Tani; Ichiro Katayama (Karger Publishers, 2014)
An elderly male noticed urticarial patches corresponding to cutaneous B cell lymphoma lesions after rituximab treatment. Along with the resolution of urticaria, the lymphoma lesions completely remitted without recurrence. In this communication, we present an interesting case and the pathophysiological findings of a wheal attack in a case with tumor remission following systemic treatment with rituximab, a monoclonal anti-CD20 antibody.